Sexuality and Slavery : Reclaiming Intimate Histories in the Americas - Harris, Leslie M. (Leslie Maria), 1965-; Berry, Daina Ramey (Book collections on Project MUSE., 2018)
In this groundbreaking collection, editors Daina Ramey Berry and Leslie M. Harris place sexuality at the center of slavery studies in the Americas (the United States, the Caribbean, and South America). While scholars have marginalized or simply overlooked the importance of sexual practices in most mainstream studies of slavery, Berry and Harris argue here that sexual intimacy constituted a core terrain of struggle between slaveholders and the enslaved. These essays explore consensual sexual intimacy and expression within slave communities, as well as sexual relationships across lines of race, status, and power. Contributors explore sexuality as a tool of control, exploitation, and repression and as an expression of autonomy, resistance, and defiance.